2003
DOI: 10.1097/00132578-200307000-00020
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Incident Retinopathy in a Diabetic and Nondiabetic Population

Abstract: General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print one copy of any publication from the public portal for the purpose of private study or research. • You may not further distribute the material or use it for any profit-making activity or commer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
40
2
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 6 publications
6
40
2
1
Order By: Relevance
“…The incidence of retinopathy in our population was slightly higher than that reported by the Hoorn Study (7.3% over 9 years) 20 and the Beaver Dam Study (6.0% over 5 years). 4 Our study population, however, was slightly older (aged 49-97 years) than the BDES population (aged 43-86 years), which could have accounted for the slightly higher incidence found.…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…The incidence of retinopathy in our population was slightly higher than that reported by the Hoorn Study (7.3% over 9 years) 20 and the Beaver Dam Study (6.0% over 5 years). 4 Our study population, however, was slightly older (aged 49-97 years) than the BDES population (aged 43-86 years), which could have accounted for the slightly higher incidence found.…”
Section: Discussioncontrasting
confidence: 76%
“…Our results are consistent with findings from the Hoorn Study. 20 The Rotterdam Study, however, reported a linear association between prevalent retinopathy and random glucose levels 46 mmol/l in their sample, which included subjects with diabetes. 31 We found that only 3.5% of baseline participants without diabetes but with retinopathy at baseline developed diabetes over the 5-year period, including those diagnosed at the 5-year examinations.…”
Section: Discussionmentioning
confidence: 94%
“…The association of obesity and diabetic retinopathy has not been consistently demonstrated in all studies. 15,16 In the WESDR, for example, higher BMI was related to retinopathy only in the type 2 participants with diabetes who did not use insulin. 16 In addition, there was a U-shaped relationship between both lower and higher BMI and retinopathy, which may reflect a "severe" phase of diabetes in underweight type 2 subjects, or these underweight patients may be a subset of late-onset type 1 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have consistently shown HbA1c to be an independent risk factor for diabetic retinopathy. 6,7,10,21,22 A higher HbA1c is associated with both increased incidence as well as progression of diabetic retinopathy. 21 The LALES study found a 22% increase in prevalence of diabetic retinopathy with 1% increase in HbA1c.…”
Section: Glycaemic Controlmentioning
confidence: 99%